A review of drug-induced renal injury - Paramanand Andankar; Krunal Shah; Vinayak Patki (Wolters Kluwer Medknow Publications, 2018)
Drug- induced acute kidney injury is common in critically ill patients. Understanding the mechanism of drug induced renal damage helps to decide appropriate preventive strategies. Identifying at risk patients and avoidance of nephrotoxic agents is of key importance. Drug dose adjusted for renal function should be used in clinical practice.